The Application of The Bamboozle Game to Improve Students’ Vocabulary Mastery - Aryansyah, Andika Dwi (Jurnal Penelitian Mahasiswa Indonesia, 2024)
Bamboozle is a fun game to play in the classroom by ringing a bell per group. The purpose of this study was to find out whether the use of Baamboozle can improve the vocabulary mastery of grade VII-A students at SMPN 1 Sukasada and to identify the factors that support and obstruct during the research. This study used grade VII-A as the subject which consisted of 31 students, with 17 boys and 14 girls. There were four meetings. The Kemmis and McTaggart methodologies were modified for use in the classroom action research approach. Tests and observation sheets were used to gather data, which were then descriptively, qualitatively, and quantitatively assessed. The results showed an increase in the percentage of students who had a high level of vocabulary mastery in each cycle, in the first cycle recorded 62.13% and in the second cycle recorded 81.74% and based on the observation sheets, there were obstruct factors during the research such as limited Wi-Fi or Internet access in the classroom, and students who did not want to discuss in groups. Meanwhile, the supporting factors during this research were the LCD Projector facilities that were functioning properly, making it easier for the students.